The development of a virtual database to provide on-line access to a large archive of clinical data. - Stevens, L. E. (American Medical Informatics Association, 1992)
The archival database of the HELP Hospital Information System at LDS Hospital is too large to be stored on line. The archival data are important for clinical and research applications. Demountable disk packs have been used to store the archival database. This method of storage has four significant disadvantages. A virtual database was developed to overcome the limitations of this data-management scheme. This virtual database enables the transparent use of appropriate low-cost network-based storage technology to provide on-line availability of the entire archive of clinical data. The virtual database successfully resolves the problems associated with disk packs, and opens the door to enhanced use of the data for clinical and research applications.